Sosialisasi Penggunaan Wordwall Sebagai Media Pembelajaran Digital kepada Guru di UPTD SDN Purwamekar - Hafiziani Eka Putri; Eva Firdausy Solihah; Rizky Purwatresna Senjaya; Abriani Larassati; Ajeng Putri Wulandari Yuwono; Hillary Ester Hutasoit (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2023)
Technology is one of the important things in various fields, especially in the field of education, in the technological age like now a professional educator must be able to keep up with the times. One of them is by making digital-based learning media, the application of learning using digital media can make it easier for students to receive learning in a fun way. So it is necessary to have a workshop for teachers in making digital-based learning media using a website called wordwall at UPTD SDN Purwamekar. This service in the form of a workshop shared with educators at UPTD SDN Purwamekar how to apply the creation of digital learning media on the wordwall website. Based on the results of the questionnaire given, 80% of the participants who attended did not know this wordwall website, and 20% already knew but had never used it. As a result of this workshop, the participants who attended came to understand and were able to apply wordwalls to learning activities.